2002
DOI: 10.1002/pd.256
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided umbilical cord occlusion using bipolar diathermy for Stage III/IV twin–twin transfusion syndrome

Abstract: Bipolar diathermy appears an effective technique for the selective reduction of monochorionic twins complicated by severe as well as preterminal TTTS, with recipient and donor fetuses being equally appropriate choices for fetocide. We suggest that for advanced-stage disease where the parents can contemplate this option, cord occlusion as a single preemptive procedure maximises the opportunity for intact survival of a single survivor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 25 publications
1
52
0
1
Order By: Relevance
“…The exclusions were because of congenital heart disease in two (severe pulmonary stenosis in a twin 1 and pulmonary atresia intact septum in a recipient at 17 weeks), while the remaining eight fetuses died in utero before detailed echocardiography could be performed, leaving a single survivor (one control MDCA and two twin-twin transfusion syndrome intrauterine deaths, and five selective terminations because of severe disease at presentation). 16 No haemodynamic differences were seen between the heavier (twin 1) and lighter twins (twin 2) in control monochorionic diamniotic twins without twin-twin transfusion syndrome (tables 2 and 3). However, intergroup analysis showed that the mean cardiothoracic ratio and Doppler peak velocities at the pulmonary valve of the recipient twins were significantly higher than those of either the donor, or twin 1/twin 2 (ANOVA p < 0.0001 and p < 0.0001, respectively).…”
Section: Resultsmentioning
confidence: 90%
“…The exclusions were because of congenital heart disease in two (severe pulmonary stenosis in a twin 1 and pulmonary atresia intact septum in a recipient at 17 weeks), while the remaining eight fetuses died in utero before detailed echocardiography could be performed, leaving a single survivor (one control MDCA and two twin-twin transfusion syndrome intrauterine deaths, and five selective terminations because of severe disease at presentation). 16 No haemodynamic differences were seen between the heavier (twin 1) and lighter twins (twin 2) in control monochorionic diamniotic twins without twin-twin transfusion syndrome (tables 2 and 3). However, intergroup analysis showed that the mean cardiothoracic ratio and Doppler peak velocities at the pulmonary valve of the recipient twins were significantly higher than those of either the donor, or twin 1/twin 2 (ANOVA p < 0.0001 and p < 0.0001, respectively).…”
Section: Resultsmentioning
confidence: 90%
“…Several techniques have been used to improve the prognosis including serial amnioreduction, 2,3 laser coagulation of anastomotic vessels, 4,5 selective fetocide 6 and cord ligation when death of one fetus appears imminent. 7 Septostomy, a rupture of the diamniotic membrane separating monozygotic twins essentially creating a monoamniotic gestation, has also been reported as a potential therapeutic modality for TTTS. 3,8 Some complications of septostomy have been reported, including cord entanglement and complete rupture of membranes of both twins, but amniotic band syndrome (ABS) associated with septostomy has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Antenatal characteristics of the five patients are shown in Table I. The median gestational age at presentation was 19 (range [17][18][19][20] weeks, and the median gestational age at laser photocoagulation was 20 (range [19][20][21][22][23] weeks. The severity of TTTS at the time of the procedure was Stage III for 3 (60%) patients and Stage II for the remaining 2 (40%) patients.…”
Section: Resultsmentioning
confidence: 99%
“…In one study of 14 patients, survival rates for the remaining twin after cord coagulation were 80%-90%, with no neurological abnormalities evident prior to discharge from hospital. (17) However, this treatment may not be an acceptable option for parents of MC twins unless used as a last resort for pre-terminal TTTS, or if parents desire a better prognosis for one twin as opposed to a guarded prognosis for both.…”
Section: Discussionmentioning
confidence: 99%